2019
DOI: 10.1111/1756-185x.13581
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of ulceration over tophi in patients with gout

Abstract: Objectives To describe clinical characteristics of ulceration over tophi in patients with gout and determine risk factors associated with ulceration. Methods Patients presenting with tophi or ulceration(s) over tophi were prospectively recruited and their clinical characteristics were recorded. Comparison of clinical characteristics and risk factors for ulceration were analyzed between groups. Results A total of 105 patients were enrolled. Thirty‐three patients with ulcerations were older, with prolonged durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…If the blood creatinine value is higher than the normal value, it indicates kidney damage; therefore, the blood CREA level can more accurately reflect renal parenchymal damage. 27,28 Our research found that the higher the CREA level, the higher the risk of renal cortex thinning in gout patients, suggesting that in the clinical diagnosis and treatment process, we could indirectly predict renal function impairment through the US changes in the renal cortex. In contrast, we could also use the blood CREA level to predict the related changes in the renal cortex indirectly.…”
Section: Discussionmentioning
confidence: 78%
“…If the blood creatinine value is higher than the normal value, it indicates kidney damage; therefore, the blood CREA level can more accurately reflect renal parenchymal damage. 27,28 Our research found that the higher the CREA level, the higher the risk of renal cortex thinning in gout patients, suggesting that in the clinical diagnosis and treatment process, we could indirectly predict renal function impairment through the US changes in the renal cortex. In contrast, we could also use the blood CREA level to predict the related changes in the renal cortex indirectly.…”
Section: Discussionmentioning
confidence: 78%
“…Glucocorticoid overuse, prolonged duration of tophi, and greater numbers of tophi are risk factors for ulceration in patients with gouty tophi. [ 10 ] The purpose of surgical treatment is to improve function, relieve pain, improve appearance, remove sinus tract and reduce tophi deposition. [ 11 ] In Case 2, we attempted surgical resection and bone cement implantation for a giant gouty tophi that severely affected function.…”
Section: Discussionmentioning
confidence: 99%
“…There had been many previous studies on the field of formation mechanism of tophi, clinically relevant risk factors, ulceration associated with tophaceous [15][16][17][18][19]. In recent years, bone destruction due to gout has attracted much attention gradually [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%